Oilseed Crops Uses, Biology and Production - Hasanuzzaman, Mirza; Nahar, Kamrun (IntechOpen, 2023)
This book contains six comprehensive chapters addressing various aspects of oilseed crop biology, production and use. The contributions summarize recent findings on oilseed crop responses to the environment, with a particular focus on rapeseed biology and stress tolerance. This book will be useful for undergraduate and graduate students, teachers, and researchers, particularly in the fields of agronomy and crop science.